Barriers to implementing circular economy learning processes in the construction sector: An analysis of Italian SMEs - Scipioni, Sara; Todisco, Lucio; Niccolini, Federico (Piccola Impresa / Small Business, 2021)
This paper examines the application of circular economy (CE) solutions in the Italian construction sector, particularly in small and medium-sized enterprises (SMEs). Specific attention is given to identifying barriers that influence the development of organizational learning (OL) processes related to circular business model (CBM) implementation. Using a qualitative method informed by grounded theory, top managers’ perceptions in Italian construction SMEs were investigated using a focus group methodology. The data analysis followed a rigorous method for iterative coding and interpretation relying on the theoretical insights found in OL and CE literature. The study highlights CBM-oriented OL barriers in the external environment, the supply chain context, and individual organizations. In particular, the study identifies culture as a critical multilevel barrier embedded in the other three dimensions. The paper offers several theoretical, managerial, and policy implications, answering a call for CE-related studies in industrial contexts. It furthermore underlines the relevance of OL processes as an essential preliminary step for CBM implementation.